Investment Decisions On Indonesia Energy Sector Companies By Capital Asset Pricing Model Model - Edison, Alva; Heikal, Jerry (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
This research was conducted to analyze the level of investment feasibility in IDX index stocks for the 2022 period using the Capital Asset Pricing Model (CAPM) method in determining investment decisions. This type of quantitative research is descriptive. The population of this study is Oil & Gas Storage, Distribution companies listed on the IDX-IC index for the period January - December 2022. The samples are 8 company shares that meet the criteria set by the researcher. This study uses SPSS linear regression analysis to determine the beta coefficient of the Capital Asset Pricing Modeling (CAPM) method and compares the expected return with the stock market rate of return during the observation period to further distinguish between efficient and inefficient stocks. The results of the observations show that 7 companies have efficient shares and 1 company that has inefficient shares which can be seen in the SML Security Market Line (SML) graph or the securities market line (GPS) of the CAPM model for efficient shares and inefficient shares.